Drug design : cutting edge approaches - Flower, Darren R. (Special publication (Royal Society of Chemistry (Great Britain)), 2002)
Pharmaceutical research draws on increasingly complex techniques to solve the challenges of drug design. Bringing together a number of the latest informatics techniques, this book looks at modelling and bioinformatic strategies; structural genomics and X-ray crystallography; virtual screening; lead optimisation; ADME profiling and vaccine design. A number of relevant case studies, focussing on techniques that have demonstrated their use, will concentrate on G-protein coupled receptors as potential disease targets. Providing details of state-of-the-art research, Drug Design: Cutting Edge Approaches will be invaluable to all drug discovery scientists, including medicinal and combinatorial chemists, molecular modellers, bio- and chemoinformaticians, and pharmacologists, amongst others.